Examination of children’s visuospatial thinking skills in domain-general learning and interpretation of scientific diagrams - Uchinokura, Shingo; Koba, Kengo (Frontiers in Education, 2022)
Visuospatial thinking in science education is an important form of thinking that involves the purposeful use of the human eyes to develop an internal representation. This study examined the visuospatial thinking skills of primary school students with two aims (1) identifying students’ cognitive levels of these skills in domain-general learning, and (2) discovering how primary school students respond to visuospatial tasks that require interpretation of a diagrammatic representation. The study also investigated whether there are differences in how male and female students answer visuospatial thinking tasks. The participants included 93 fourth-grade students (8–9 years old), including 51 male and 42 female students, from a public primary school in Japan. The participants completed two types of paper-pencil tests. The first test required participants to complete the Wide-range Assessment of Vision-related Essential Skills (WAVES), a domain-general test that measures visual perception and eye-hand coordination skills. In the second test, students answered questions about the relationship between the movement of the sun and the behaviors of solar cells located in different places by interpreting a diagrammatic representation. Female students outperformed male students in one of the four WAVES index scores; otherwise, no other statistically significant differences were found. A small number of students had low visuospatial perception scores. When students were asked to explain their reasoning regarding how the solar cells worked based on their interpterion of the diagram, only a few answered correctly using perspective-taking and/or visualizing. Other students struggled to provide their reasoning, even if they had factual knowledge. Some students held an alternative conception of sunlight intensity and the sun’s path in the sky. They worked through the problem from their alternative conceptions without reference to visuospatial information or taking different perspectives from the diagram. No statistically significant differences were found in the relationship between achievement in the domain-general test and the number of correct answers in the domain-specific test. The study’s findings imply that students should be encouraged to practice visuospatial thinking to overcome previously held alternative conceptions. Furthermore, science education should emphasize the concept of space and teach conventional knowledge on different representation types. Further research on students’ learning progress in visuospatial thinking that includes alternative conceptions such as the students’ domain-specific knowledge is recommended.